Insidensi Serangan dan Perkembangan Populasi Hama Invasif, Spodoptera frugiperda (J. E Smith) (Lepidoptera: Noctuidae) pada Tanaman Jagung dan Sorgum di Bali - SIMANJUNTAK, CRISTINE LAURINE; SUMIARTHA, I KETUT; YULIADHI, KETUT AYU; SUPARTHA, I WAYAN (Agrotrop : Journal on Agriculture Science, 2022)
Incidence of Attacks and Population Development of Invasive Pests, Spodoptera frugiperda (J.E Smith) (Lepidoptera: Noctuidae) on Corn and Sorghum Crops in Bali.   Spodoptera frugiperda is known as an invasive pest which now become important pest on corn crops in Indonesia and Bali in particular, but in this study the Spodoptera frugiperda was also found to attack sorghum. This study used purposive survey method and on land that had been fixed. Plant sampling was carried out in all regencies of Bali Province by means of diagonal sampling. The size of unit sample was 2 x 2m and the number of plants observed was 20 plants. The results of this study showed that the incidence of S. frugiperda attack has been observed on plant beds in all districts/cities in Bali which is indicated by symptoms of attack and abundance of S. frugiperda population on corn and sorghum in the field. The highest abundance of S. frugiperda larvae population was in sweet corn in Klungkung Regency as much as 38.67 heads, and the lowest was in sorghum numbu in Tabanan Regency as many as 27.00 individuals per observation plot. Population development of egg groups was found in plants aged 1 (MST) while larvae of S. frugiperda showed the same pattern in sweet corn, sticky rice and pipil plants and the peak of larval population occurred in plants aged 4 WATS respectively. While the peak population of larvae in sorghum plants occurred at 5 WAP and imago populations in sweet corn were found in sweet corn plants at 2 WAP and glutinous corn at 4 WAP. The highest percentage of S. frugiperda attack was on sweet corn with an average attack of 43% per observation plot and the lowest on sorghum numbu with an average of 25% per observation plot.